Proceso de creación del diseño de producción para el piloto de una miniserie web ecuatoriana de ciencia ficción de bajo presupuesto - Castro Palma, Francis Iván (2019)
This work analyzes the processes within each stage of production design and the importance they have in the outcome of an audiovisual product. It focuses particularly on those belonging to the science fiction genre, and subsequently contrasts them with those that took place in the production design of VOYAGER, pilot episode and spin off from the forthcoming series CERO. Through the author is own experiences along with those of professional production designers, this work explores and draws a motivation to understand everything that entails the creation of the visuals and the aesthetic style of a movie. It also establishes a starting point, a practical advice manual for young filmmakers who immerse themselves on similar projects, emphasizing, but not exclusively, on those which have limited resources.